Інструментарій та механізм державного регулювання інвестиційного забезпечення розвитку реального сектору економіки - Ортіна, Ганна Володимирівна; Ортина, Анна Владимировна; Ortina, Hanna (My University, 2017)
UK: Значні ризики у вітчизняній економіці та несприятливі умови державної політики не стимулюють залучення прямих іноземних інвестицій, позбавляють країну можливостей придбання сучасних технологій, новітнього досвіду у сфері управління. У статті запропоновано інструментарій та механізм державного регулювання залучення іноземних інвестицій в реальний сектор економіки України за джерелами: іноземні, спеціалізовані, кредитування, кошти промислових і торгових компаній, конвертація українських акцій в американські депозитарні розписки. EN: Significant risks in the domestic economy and unfavorable conditions of state policy do not stimulate the attraction of foreign direct investment, deprive the country of opportunities to acquire modern technology, the latest experience in management. The article proposes an instrument and mechanism of state regulation of attracting foreign investments into the real sector of economy of Ukraine by sources: foreign, specialized, lending, funds of industrial and trading companies, conversion of Ukrainian shares into US depositary receipts. The level of inflow of investments into the real sector of the economy of Ukraine is analyzed and the implementation of state regulation of their attraction by the following sources is proposed: direct investments from foreign countries operating through the National Bank or specially created for this purpose their institutions; funds of investment funds specializing in the financing of promising projects; long$term loans from foreign private commercial and investment banks; funds of foreign pension funds and insurance companies; means of industrial and trading companies; investments through the conversion of Ukrainian shares into US Depository Certificates (ADRs) or Global (GDR) Depositary Receipts.
Tool and mechanism of governmental regulation of investment development in real economy sector
Keywords: державне регулювання; іноземні інвестиції; інвестиційна діяльність; інвестиційні проекти; капітал; кредитування; механізм; реальний сектор економіки; state regulation; foreign investments; investment activity; investment projects; capital; lending; mechanism; real sector of economy